Induction of Nectriapyrone Biosynthesis in the Rice Blast Fungus Pyricularia oryzae by Disturbance of the Two‐Component Signal Transduction System. (23rd January 2019) - Motoyama, Takayuki; Nogawa, Toshihiko; Hayashi, Toshiaki; Hirota, Hiroshi; Osada, Hiroyuki
Abstract: Most fungal secondary metabolism genes are poorly expressed under laboratory conditions. Nectriapyrones are known as secondary metabolites produced mainly by symbiotic fungi, including endophytes and plant pathogens. Herein, we show the induction of nectriapyrone production in the rice blast fungus Pyricularia oryzae . The two‐component signal transduction system was disturbed by disrupting OSM1 and PoYPD1, which encoded a HOG MAP kinase and a His‐containing phosphotransfer (HPt) protein, respectively. This induced the production of two polyketide compounds: nectriapyrone and its hydroxylated analogue. The nectriapyrone biosynthetic gene cluster consists of a polyketide synthase gene ( NEC1 ) and an O‐methyltransferase gene ( NEC2 ). Overexpression of the two genes induced overproduction of nectriapyrone and five nectriapyrone analogues, including a new derivative. Nectriapyrone production was not required for the infection of rice. The structure of nectriapyrone is similar to that of the germicidins produced by Streptomyces spp., and nectriapyrone inhibited the growth of Streptomyces griseus . Abstract : Disturbance in the fungus : Most fungal secondary metabolism genes are poorly expressed under laboratory conditions. Herein, the induction of nectriapyrone production in the rice blast fungus Pyricularia oryzae is shown by disturbing the two‐component signal transduction system.